Association between vitamin intake and prostate cancer: a cross-sectional study - Pan, Sen; Wang, Chuanlin; Sun, Wei; Zhang, Xin (Frontiers in Nutrition, 2025)
BackgroundAs micronutrients, vitamins play a critical role in maintaining normal physiological functions. However, the impact of different types of vitamins on PCa remains controversial. This study aimed to investigate the association between vitamin intake and PCa using a cross-sectional design.MethodsWe conducted a cross-sectional analysis of 14,977 adult men using data from the National Health and Nutrition Examination Survey (NHANES) collected between 2007 and 2018. Dietary intake was assessed using 24-h dietary recall interviews. Multivariate weighted logistic regression models were used to analyze the relationship between vitamin intake and PCa. Restricted cubic spline (RCS) was conducted to evaluate the non-linear relationship. We performed a trend test to examine the association between vitamin intake and PCa risk, and conducted an interaction analysis stratified by group covariates. The covariates included age, race, body mass index, educational attainment, the ratio of family income to poverty, alcohol intake, smoking status, diabetes, and hypertension.ResultsThe study encompassed 10 vitamins with three ways of intake: diet, supplement, and total (diet plus supplement). In the fully adjusted model, the quartile-based analysis showed that individuals in the highest quartile of dietary retinol intake had a significantly increased risk of PCa (OR = 1.76, p = 0.027), while higher supplement intake of vitamin B1 (OR = 0.38, p = 0.036) and vitamin B2 (OR = 0.35, p = 0.016) was associated with a lower risk. In the continuous variable analysis, supplement intake of vitamin B9 (OR = 0.65, p = 0.049), vitamin B12 (OR = 0.83, p = 0.030), and total vitamin B12 (OR = 0.82, p = 0.037) were inversely associated with PCa risk after full adjustment. We identified significant non-linear associations between dietary intake of vitamins A, B6, B12, and C and PCa risk using RCS analysis. There is an interaction between supplementation, total vitamin B12 intake, and age groups.ConclusionTaken together, our study provides the latest evidence for vitamin intake and PCa prevention. Large-scale randomized controlled trials are still needed to provide additional evidence.